Association of antibiotic duration and all-cause mortality in a prospective study of patients with ventilator-associated pneumonia in a tertiary-level critical care unit in Southern India - Karthik Gunasekaran; Ramya Iyyadurai; Bijesh Yadav; Sowmya Sathyendra; Kishore Pichamuthu; Samuel George Hansdak; Nivin Daniel Stanley; Jonathan Arul Jeevan; Vignesh Kumar Chandiraseharan (BMJ Open, 2024)
Objectives To estimate all-cause mortality in ventilator-associated pneumonia (VAP) and determine whether antibiotic duration beyond 8 days is associated with reduction in all-cause mortality in patients admitted with VAP in the intensive care unit.Design A prospective cohort study of patients diagnosed with VAP based on the National Healthcare Safety Network definition and clinical criteria.Setting Single tertiary care hospital in Southern India.Participants 100 consecutive adult patients diagnosed with VAP were followed up for 28 days postdiagnosis or until discharge.Outcome measures The incidence of mortality at 28 days postdiagnosis was measured. Tests for association and predictors of mortality were determined using χ2 test and multivariate Cox regression analysis. Secondary outcomes included baseline clinical parameters such as age, underlying comorbidities as well as measuring total length of stay, number of ventilator-free days and antibiotic-free days.Results The overall case fatality rate due to VAP was 46%. There was no statistically significant difference in mortality rates between those receiving shorter antibiotic duration (5–8 days) and those on longer therapy. Among those who survived until day 9, the observed risk difference was 15.1% between both groups, with an HR of 1.057 (95% CI 0.26 to 4.28). In 70.4% of isolates, non-fermenting Gram-negative bacilli were identified, of which the most common pathogen isolated was Acinetobacter baumannii (62%).Conclusion In this hospital-based cohort study, there is insufficient evidence to suggest that prolonging antibiotic duration beyond 8 days in patients with VAP improves survival.